Unfunded Mandates and Fiscal Structure: Empirical Evidence from a Synthetic Control Model. (1st November 2017) - Ross, Justin M.
Abstract: An unfunded expenditure mandate occurs when governments are required to provide a good or service by a higher level of government without an accompanying revenue source. There are no empirical studies providing causal evidence on the fiscal influence of intergovernmental mandates. This article examines Florida's 1990 constitutional Amendment 3, which sought to limit unfunded state mandates on municipal and county governments. The synthetic control method, an empirical technique for drawing causal inferences from case studies, estimates the effect of Amendment 3 on state expenditures and total transfers to local governments. The results indicate that state expenditures increased by an annual average of 9.5 percent, while state transfers to all local governments were unaffected. However, the municipalities protected by Amendment 3 saw intergovernmental revenue from the state decrease by 10 percent annually, which suggests that remaining mandates likely targeted special districts, encouraging the fragmentation of local public service delivery .